Papillary tumor of the pineal region: a distinct molecular entity - Heim, Stephanie; Sill, Martin; Jones, David T. W.; Vasiljevic, Alexandre; Jouvet, Anne; Fèvre‐Montange, Michelle; Wesseling, Pieter; Beschorner, Rudi; Mittelbronn, Michel; Kohlhof, Patricia; Hovestadt, Volker; Johann, Pascal-David; et al. (Brain pathology, 2016)
Papillary tumor of the pineal region (PTPR) is a neuroepithelial brain tumor, which might pose diagnostic difficulties and recurs often. Little is known about underlying molecular alterations. We therefore investigated chromosomal copy number alterations, DNA methylation patterns and mRNA expression profiles in a series of 24 PTPRs. Losses of chromosome 10 were identified in all 13 PTPRs examined. Losses of chromosomes 3 and 22q (54%) as well as gains of chromosomes 8p (62%) and 12 (46%) were also common. DNA methylation profiling using Illumina 450k arrays reliably distinguished PTPR from ependymomas and pineal parenchymal tumors of intermediate differentiation. PTPR could be divided into two subgroups based on methylation pattern, PTPR group 2 showing higher global methylation and a tendency toward shorter progression-free survival (P = 0.06). Genes overexpressed in PTPR as compared with ependymal tumors included SPDEF, known to be expressed in the rodent subcommissural organ. Notable SPDEF protein expression was encountered in 15/19 PTPRs as compared with only 2/36 ependymal tumors, 2/19 choroid plexus tumors and 0/23 samples of other central nervous system (CNS) tumor entities. In conclusion, PTPRs show typical chromosomal alterations as well as distinct DNA methylation and expression profiles, which might serve as useful diagnostic tools.